ANALYSIS OF LEGAL PROTECTION FOR CONSUMERS FROM UNCERTIFIED HALAL FOODS AND BEVERAGES - Qayyim, Muhammad; Riyanto, Slamet; Mawadi, Habloel (Fakultas Hukum, Universitas Islam As-Syafi'iyah, 2022)
Legal protection for consumers for the distribution of food and beverages that are not halal certified still does not have clear information that can create bad impacts that commonly occur, including regarding the quality or quality of goods, information that is not clear and even misleading, counterfeiting and so on, by following and obeying laws and regulations, including protecting the halalness of a food and beverage to be circulated, it will create the welfare of consumers. Since the enactment of laws and regulations related to these matters, producers have begun to make changes and implement these laws. These changes, when viewed from the perspective of everyday life, have not been effective enough and the producers have not provided product information openly. From information that is not clear and even misleading, forgery and so on. Formulation of the problem in this study (1) What is the form of legal protection for consumers according to the law on halal product guarantees?, (2) What is the responsibility of business actors for food and beverage products that are not halal-certified?. The purpose of this study is to determine the form of legal protection for consumers according to the law on halal product guarantees and to determine the responsibility of business actors for food and beverage products that are not halal certified. This legal research is classified as normative juridical research. The data collected in this research is through research with premier legal materials, secondary legal materials, and tertiary legal materials. Primary legal materials are legal materials that are authoritative. Based on the results of the analysis of legal protection against consumers for the distribution of food and beverages that are not halal certified to consumers, especially food and beverages that are not halal certified that are not in accordance with the provisions of the legislation. The form of accountability of business actors by means of civil law and criminal law. Civil law in question is compensation after a lawsuit is against the law and criminal law in question is that business actors can be criminally prosecuted in court.